Pretreatment HIV drug Resistance and Treatment Failure in Non-Italian HIV-1-Infected Patients Enrolled in ARCA. Issue 2 (February 2020) - Bavaro, Davide Fiore; Carlo, Domenico Di; Rossetti, Barbara; Bruzzone, Bianca; Vicenti, Ilaria; Pontali, Emanuele; Zoncada, Alessia; Lombardi, Francesca; Di Giambenedetto, Simona; Borghi, Vanni; Pecorari, Monica; Milini, Paola; et al.
Background: An increase in pretreatment drug resistance (PDR) to first-line antiretroviral therapy (ART) in low-income countries has been recently described. Herein we analyse the prevalence of PDR and risk of virological failure (VF) over time among migrants to Italy enrolled in ARCA. Methods: HIV-1 sequences from ART-naive patients of non-Italian nationality were retrieved from ARCA database from 1998 to 2017. PDR was defined by at least one mutation from the reference 2009 WHO surveillance list. Results: Protease/reverse transcriptase sequences from 1, 155 patients, mainly migrants from sub-Saharan Africa (SSA; 42%), followed by Latin America (LA; 25%) and Western countries (WE; 21%), were included. PDR was detected in 8.6% of sequences (13.1% versus 5.8% for B and non-B strains, respectively; P <0.001), 2.1% of patients carried a PDR for protease inhibitors (PIs; 2.1% versus 2.3%; P =0.893), 3.9% for nucleoside/ nucleotide reverse transcriptase inhibitors (NRTIs; 6.8% versus 2.1%; P <0.001) and 4.3% for non-nucleoside/ nucleotide reverse transcriptase inhibitors (NNRTIs; 6.3% versus 3.1%; P =0.013). Overall, prevalence of PDR over the years remained stable, while it decreased for PIs in LA ( P =0.021) and for NRTIs ( P =0.020) among migrants from WE. Having more than one class of PDR ( P =0.015 versus absence of PDR), higher viral load at diagnosis ( P =0.008) and being migrants from SSA ( P =0.001 versus WE) were predictive of VF, while a recent calendar year of diagnosis ( P <0.001) was protective for VF. Conclusions: PDR appeared to be stable over the years in migrants to Italy enrolled in ARCA; however, it still remains an important cause of VF together with viral load at diagnosis.